Cu3(BTC)2 metal organic framework as a promising adsorbent for operative exclusion of toxic dyes and herbicide - R. Sakthivel; Ponnusamy Palanisamy; Senthil Kumaran Selvaraj; Zaher Abdel Baki; Sai Saraswathi Vijayaraghavalu (Results in Materials, 2024)
Synthetic organic dyes and herbicide pollutants pose a significant threat to water quality due to their high solubility in water and widespread industrial discharge. In water conservation developments, the Metal-Organic Frameworks (MOFs) are considered confident and substantial for the exclusion of toxic organic dyes, due to their multi-potential assets of cost-effective, high pore volume, high thermal stability, easy adaptation to toxic dye molecules, and most of them are stable in water, etc. Hence, the green synthetic methodology was employed for the combination of Cu3(BTC)2 MOF, which is draped with carboxylate functionality ligands, as an adsorbent to remove the hazardous dyes of Methyl Orange (MO), Acid Yellow (AY), and toxic herbicide of Atrazine (ATZ) from contaminated wastewater. As-reported Cu3(BTC)2 was evidently characterized by XRD, FTIR, TGA, XPS, SEM, and EDAX analysis. The equilibrium adsorption capacity (Qe) value of as-reported Cu3(BTC)2 for AY, MO, and ATZ was better in comparison with the formerly reported adsorbent. The high adsorption capacity of Cu3(BTC)2 for AY (777 mg/g), MO (903 mg/g), and ATZ (484 mg/g) is principally explained by π-π and electrostatic interaction. As a result, Cu3(BTC)2 is reported and proposed as a suitable adsorbent for the abolition of toxic dyes and herbicides from contaminated water.